Novel Anderson-type [TeMo6O24]6−-based metal–organic complexes tuned by different species and their coordination modes: assembly, various architectures and properties. Issue 6 (8th January 2016) - Wang, Xiuli; Sun, Junjun; Lin, Hongyan; Chang, Zhihan; Tian, Aixiang; Liu, Guocheng; Wang, Xiang
Abstract : Four novel Anderson-type polyoxometalate [TeMo6 O24 ] 6− -based metal–organic complexes were hydrothermally synthesized and characterized, which show fluorescence, electrochemical and photocatalytic properties. Abstract : Four novel Anderson-type polyoxometalates (POMs) [TeMo6 O24 ] 6− (TeMo6 )-based metal–organic complexes (MOCs), namely, H2 [Zn4 (3-Hdpyp)2 (TeMo6 O24 )2 (H2 O)16 ]·6H2 O (1 ), [Zn3 (3-dpyb)2 (TeMo6 O24 )(H2 O)12 ]·8H2 O (2 ), [Cu2 (4-Hdpyp)2 (TeMo6 O24 )(H2 O)6 ]·4H2 O (3 ), and [Cu3 (3-dpyp)2 (TeMo6 O24 )(H2 O)8 ]·4H2 O (4 ) (3-dpyp = N, N ′-bis(3-pyridinecarboxamide)-1, 3-propane, 3-dpyb = N, N ′-bis(3-pyridinecarboxamide)-1, 4-butane, 4-dpyp = N, N ′-bis(4-pyridinecarboxamide)-1, 3-propane), were hydrothermally synthesized and structurally characterized by single-crystal X-ray diffraction, IR spectra, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). In complex1, two TeMo6 polyoxoanions bridge Zn II ions to generate a discrete tetranuclear zinc complex H2 [Zn4 (3-Hdpyp)2 (TeMo6 O24 )2 (H2 O)16 ]. In2, the TeMo6 anions connect the metal–organic units [Zn3 (3-dpyb)2 ] 6+ to form an Anderson-type TeMo6 -based wave-like metal–organic chain. Both the discrete tetranuclear subunits in1 and 1D wavy chains in2 were further extended to 2D supramolecular networks through the hydrogen bonding interactions. In complex3, the TeMo6 anions link the metal–organic units [Cu2 (4-Hdpyp)2 ] 6+ to construct a 2D layer, which is further extended to a 3D supramolecular framework by the hydrogen bonding interactions. In complex4, the TeMo6 polyoxoanions bridge the Cu II ions to generate a 2D Cu-TeMo6 inorganic layer, which is further linked by the μ2 -bridging 3-dpyp ligands to form a 3D metal–organic framework. The effects of various coordination modes of TeMo6 polyanions and the bis-pyridyl-bis-amide ligands, as well as the central metals on the structures of the title complexes have been discussed. Besides, the fluorescence, electrochemical properties and photocatalytic activities of the title complexes have been investigated in detail.